The effect of respiratory muscle training on swimming performance: a systematic review and meta-analysis - Liu, Shunfang; Gou, Pengpeng; Lin, Menglong (Frontiers in Physiology, 2025)
IntroductionRespiratory muscle training, which targets the inspiratory and/or expiratory muscles to enhance respiratory efficiency, is recognized as a method for improving athletic performance; however, its effectiveness in enhancing swimming performance remains controversial. This study aimed to evaluate the effects of respiratory muscle training on swimming performance.MethodsMethodology followed the PRISMA guidelines. A comprehensive literature search was conducted in eight databases (Web of Science, PubMed (comprising MEDLINE and PubMed Central), SPORTDiscus, ScienceDirect, Scopus, Cochrane Library, Embase, and ProQuest) and supplemented with manual searches of other sources (e.g., Google Scholar) up to 22 May 2025. Studies were eligible for inclusion if they met the following criteria: (a) participants were healthy individuals without diagnosed disease or disability; (b) the intervention involved respiratory muscle training compared to a sham or control condition in a randomized controlled trial or controlled clinical trial; (c) swimming performance was reported as an outcome with sufficient data to compute effect sizes; and (d) the full text was available.ResultsResults of this systematic review revealed that of the 1,044 articles retrieved from the search strategy, 10 met the inclusion criteria. Meta-analysis indicated that respiratory muscle training significantly improved swimming performance, with low heterogeneity and no evidence of publication bias. Among the included studies, respiratory muscle training protocols were typically conducted at 50%–80% of maximal inspiratory pressure for 6–8 weeks, with a frequency of 3–14 sessions per week. However, substantial variability in training frequency, progression, and duration limited direct comparisons between interventions. Due to inconsistent and limited reporting, subgroup analysis based on gender, stroke style, or competitive level could not be performed.DiscussionRespiratory muscle training appears to be an effective adjunct to swimming training, contributing to improved performance. Future studies should prioritise protocol standardisation, elucidate the dose-effect relationship, and explore moderating factors such as gender, stroke type, and training status. Registered on PROSPERO (registration number: CRD420251051091).Systematic Review RegistrationIdentifier CRD420251051091.